Comparison of extracardiac conduit and lateral tunnel for functional single‐ventricle patients: A meta‐analysis. (28th August 2017) - Lin, Zhiyong; Ge, Hanwei; Xue, Jiyang; Wu, Guowei; Du, Jie; Hu, Xingti; Zhao, Qifeng
Abstract: Objective: This study aims to assess and compare the early and long‐term effects of extracardiac conduit (EC) and lateral tunnel (LT) in patients with a functional single ventricle through meta‐analysis. Design: A systematic search was performed in PubMed, Embase, Cochrane Library, CNKI, VIP, CBM, and WanFang databases for papers that were published until August 1, 2016. Cochrane systematic review method was used for paper screening and information retrieve, and RevMan 5.3 software was applied for the meta‐analysis. Results: Data for 10 studies with a total of 3814 patients were retrieved. The advantages of EC comparing to LT include: lower 30 day postsurgery supraventricular arrhythmia incidence (Relative Risk [RR] = 0.31 [0.17, 0.55], P < .001), lower protein loss enteropathy incidence (RR = 0.33 [0.11, 0.96], P = .04), and requiring no cardiopulmonary bypass. However, the chest drainage time was longer (mean difference [MD] = 1.99 [1.83, 2.15], P < .001) in EC. There were no significant differences in early postoperative mortality, long‐term mortality, long‐term arrhythmia, Fontan takedown, ventilator‐assisted ventilation, ICU stay, thrombosis, pleural effusion, and pericardial effusion between EC and LT. Conclusions: EC had a lower incidence of supraventricular arrhythmia (30 days after operation) and the rate of protein losing enteropathy than LT, and requiring no cardiopulmonary bypass. These show that EC has an advantage over the LT in patients with a functional single ventricle.